Fresno County Counsel Office Party for Pat Flynn's Wedding Gift - Watkins, Howard::::::::: (1986)
Sharon St. John, Vincent McGraw, Peggy Smith, Leticia Aleman, Barbara Christiansen, Linda ?, Mary Herrick, County Counsel Max Robinson, Phil Jay, John Slutter, Vickie Stoutingberg and Pat Flynn opening office wedding gift of a crystal wine decanter